Determining working parameters for the Hall-effect thruster with permanent magnets - Petrenko, Olexandr; Pererva, Viktor; Maslov, Viktor (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is a Hall-effect thruster with a magnetic system on permanent magnets with minimal power consumption of electric energy, designed by Flight Control LLC (Ukraine). The task addressed in the study was to minimize the power consumed by the engine by excluding electromagnets from the engine’s magnetic system and using only permanent magnets in the magnetic system. To solve this task, a laboratory model of a Hall-effect thruster with permanent magnets was built and the operating parameters and characteristics of the engine were experimentally determined. As a result of laboratory studies of the operating parameters of the engine with permanent magnets, the volt-ampere characteristics of the engine discharge were obtained at fixed working gas (xenon) flow rates. The dependences of engine thrust on the mass flow rate of the working gas at fixed discharge voltages were also obtained. Based on the experimental data, the dependences of specific impulse of the engine anode block on the discharge voltage, as well as the dependences of efficiency of the engine anode block on discharge voltage and the working substance flow rates were calculated. The studies have shown that in Hall-effect thrusters of low thrust, in order to minimize the specific power as part of the magnetic system, it is quite possible to use permanent magnets. In particular, for the power range (100–200) W, the values of thrust (3–10) mN, specific impulse (700–1350) s, and efficiency of the anode block (25–37) % were achieved, which corresponds to the parameters of the considered prototypes with the conventional and combined structure of the magnetic system. The results of the work could be used in practice when designing Hall-effect thrusters of low specific power